Penerapan Model Circuit Learning dalam Pembelajaran IPA di Madrasah Ibtidaiyah - Rohmah, Annisa Nidaur; Mufidah, Imro’atul (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2022)
This study aims to determine the application of the Circuit Learning Model in science learning at Madrasah Ibtidaiyah. This study is a qualitative research descriptive analysis of data collection methods used are observation, interviews, and documentation. The results of the research are the application of the circuit learning model in science learning including Conducting questions and answers about the topics discussed, pasting pictures about the topic on the blackboard, asking questions about pasted pictures, pasting concept maps that have been made, explaining pictures and concept maps that have been made. have been pasted (visualization activities), Divide students into several groups, give worksheets to each group, explain that each group must fill in the worksheets and fill out part of the concept map according to their own language, explain that the concept map that has been worked on will be presented carry out the presentation of the concept map section that has been done, provide reinforcement in the form of praise or prizes for good presentation results and encourage those who have not received praise or prizes to try harder and explain the results of the student discussions. in order to broaden the horizons of students.